ANALISIS FAKTOR KEUANGAN DAN NON KEUANGAN YANG MEMPENGARUHI PENERIMAAN OPINI AUDIT GOING CONCERN - Gea Cherlita Putrady; Haryanto Haryanto (Diponegoro Journal of Accounting, 2014)
This study aims to analyze and provide empirical evidence of the influence of the condition, debt default, compaqny’s growth, auditor client tenure, opinion shopping, audit lag, and disclosure on the probability of receiving going concern opinion. Hypothesis proposed (1) corporate financial condition affect the probability of accepting the opinion of going concern,(2) debt default effect on acceptance going concern opinion, (3) company’s growth effect on acceptance going concern opinion, (4) auditor client tenure influence on acceptance going concern opinion,(5) opinion shopping influence on acceptance going concern opinion,(6) audit lag influence on acceptance going concern opinion,(7) disclosure affect the probability of accepting the opinion of going concern. This study used 22 manufacturing companies listed on the Indonesian Stock Exchange (BEI) in the year 2006 to 2012, sample obtained by purposive sampling. Data were analyzed using logistic regression anylisis.The results of this research showed that the facto company’s financial, debt default, and disclosure have a significant influence on acceptance going concern opinion.While the other factors, the company’s growth, auditor client tenure, opinion shopping, and audit lag are not proven having a significant influence for Timeliness.